Therapeutic potential of tumor treating fields for malignant brain tumors - Youyou Zhou; Xiaoqing Xing; Jinyun Zhou; Han Jiang; Peili Cen; Chentao Jin; Yan Zhong; Rui Zhou; Jing Wang; Mei Tian; Hong Zhang (Cancer Reports, 2023)
Abstract Background Malignant brain tumors are among the most threatening diseases of the central nervous system, and despite increasingly updated treatments, the prognosis has not been improved. Tumor treating fields (TTFields) are an emerging approach in cancer treatment using intermediate‐frequency and low‐intensity electric field and can lead to the development of novel therapeutic options. Recent Findings A series of biological processes induced by TTFields to exert anti‐cancer effects have been identified. Recent studies have shown that TTFields can alter the bioelectrical state of macromolecules and organelles involved in cancer biology. Massive alterations in cancer cell proteomics and transcriptomics caused by TTFields were related to cell biological processes as well as multiple organelle structures and activities. This review addresses the mechanisms of TTFields and recent advances in the application of TTFields therapy in malignant brain tumors, especially in glioblastoma (GBM). Conclusions As a novel therapeutic strategy, TTFields have shown promising results in many clinical trials, especially in GBM, and continue to evolve. A growing number of patients with malignant brain tumors are being enrolled in ongoing clinical studies demonstrating that TTFields‐based combination therapies can improve treatment outcomes.